Radioepidemiologic and experimental evidence: Health risks associated with radiofrequency radiation exposure - Roslan, Umar; Nurulhuda, Mohammad Yusoff; Siti Maisarah, Aziz; Azmi, Hassan; Farhana, Mohamad Yussof (2019)
Public exposure to Electromagnetic Radiation, which abbreviatedly known as EMR is a recurring phenomenon and it becomes among the factors contributing to the public concerns. EMR represents a new technology, such as base stations, overhead power lines and other sources of exposure, that is difficult to control by the affected individual. Non-ionizing and ionizing radiation are two major divisions of the electromagnetic spectrum. Both kinds of radiation can be differentiated based on which one has enough energy to knock electrons off atoms upon collision, as well as capable to give out lower-energy harm, such as breaking chemical bonds in molecules. Ionizing radiation is a type of radiation that has a short wavelength to interact with the electrons in biological chemicals. Alpha, beta, and gamma rays are examples of ionizing radiation. The literature on RF effects also focused on the human factor and health parameters, both from the laboratory and epidemiological study perspectives. The presence of this communication technology has given rise to media and public concerns about the possibility of RF radiation emitted by computers, phones and base stations that might cause a rise in diseases that affect the reproductive system, neurobehavioral parameters and various forms of cancers, especially brain tumours. More recently, concerns about the possible effects culminating from the massive development of base stations coupled with increasing use of mobile phones have begun to appear due to the enormous growth of wireless mobile communication, mainly handheld devices. This has led to increased apprehension as to whether non-ionizing radiation (NIR) used in present technologies could have short, medium and long-term biological effects.